Gambaran Bimbingan Orang Tua dalam Membentuk Kemandirian Anak Usia Dini - Effendi, Annisa Yuliani; Syuraini, Syuraini (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is motivated by the success of parents in shaping the independence of early childhood in Jorong Nagari Gadang Akabiluru Subdistrict. The independence of early childhood is known from the results of interviews with parents and data from the Jorong Nagari Gadang school. Researchers suspect that the reason for the good independence of children in Jorong is because of guidance from parents. This type of research is quantitative descriptive research. The population in this study were parents (mothers) who had early childhood totaling 26 people. The sampling technique used was a proportionate stratified random sampling of 21 people. The technique of collecting data uses a questionnaire. While the data collection tool uses a list of statements (questionnaires). The data analysis technique uses the percentage formula. The results showed parental guidance in shaping the independence of early childhood through (1) Parental support in shaping children's independence is classified very well (2) Exemplary parents in shaping children's independence are classified very well, and (3) Communication of parents in forming the independence of children is classified as very good.